IMPROVING INDONESIAN STUDENTS’ RHETORICAL SKILLS THROUGH SUGGESTOPEDIA - Suprapto Suprapto; Rio Kurniawan (Universitas Bengkulu, 2020)
This study aims to improve students’ rhetoric skills of a class at the Indonesian Education Study Program Faculty of Teacher Traning and Education University of Bengkulu, in the academic year of 2018/2019. This research uses a qualitative approach with descriptive method to describe the conditions of rhetoric learning using the method sugestopedia for students from A class of Indonesian Education Study Program Faculty of Teacher Training and Education University of Bengkulu, academic year 2018/2019 was employed. Based of the research results in the first cycle there are advantages in the application of the suggestopedia method in learning speaking skill, namely; 1. The existence of student confidence and motivation in learning rhetoric. 2. By using the Suggestopedia Method, students can feel comfortable in learning, so that the imagination of students is more better. In the research conducted in the first cycle there are also deficiencies, namely the example of rhetoric given to students using simple aspects as that students tend to rhetoric based on the aspects used in the example of the rhetoric. The results of the data analysis of the second cycle of learning with the application of the suggestopedia method, obtained data; 37 students scored above 70 and mastery learning 92.5%. As the researcher stopped this class action research until the second cycle, because the research indicators had been reached.